The changing contribution of smoking to educational differences in life expectancy: indirect estimates for Finnish men and women from 1971 to 2010. Issue 3 (30th November 2012) - Martikainen, Pekka; Ho, Jessica Y; Preston, Samuel; Elo, Irma T
Abstract : Background: We estimated the contribution of smoking to educational differences in mortality and life expectancy between 1971 and 2010 in Finland. Methods: Eight prospective datasets with baseline in 1970, 1975, 1980, 1985, 1990, 1995, 2000 and 2005 and each linked to a 5-year mortality follow-up were used. We calculated life expectancy at age 50 years with and without smoking-attributable mortality by education and gender. Estimates of smoking-attributable mortality were based on an indirect method that used lung cancer mortality as a proxy for the impact of smoking on mortality from all other causes. Results: Smoking-attributable deaths constituted about 27% of all male deaths above age 50 years in the early 1970s and 17% in the period 2006–2010; these figures were 1% and 4% among women, respectively. The life expectancy differential between men with basic versus high education increased from 3.4 to 4.7 years between 1971–1975 and 2006–2010. In the absence of smoking, these differences would have been 1.5 and 3.4 years, 1.9 years (55%) and 1.3 years (29%) less than those observed. Among women, educational differentials in life expectancy between the most and least educated increased from 2.5 to 3.0 years. This widening was nearly entirely accounted for by the increasing impact of smoking. Among women the contribution of smoking to educational differences had increased from being negligible in 1971–1975 to 16% in 2006–2010. Conclusions: Among men, the increase in educational differences in mortality in the past decades was driven by factors other than smoking. However, smoking continues to have a major influence on educational differences in mortality among men and its contribution is increasing among women.